PROGRAM DUKUNGAN PERILAKU POSITIF (DPP) UNTUK MENINGKATKAN KETERAMPILAN SOSIAL ANAK DENGAN GANGGUAN PERILAKU PADA SETING SEKOLAH - , AINI MAHABBATI; , Prof. Dr. Sofia Retnowati ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Children with conduct disorder have several problems in social interaction and academic that is caused by their misbehavior and poor social skills. Schoolbased intervention program is needed to enhance their social skills. This research applied School-based Positive Behavior Support (PBS) in Prayuwana Special School with three students as subjects. Exploration of program implementation and improvement process of their social skills became objective of this research. This research approach was qualitative action research method by Kemmis and McTaggart. This model consists of four stages: planning, acting, observing, and reflecting. PBS intervention was conducted in two cycles of action. Research collaborator was the classroom teacher, some other teachers, and principal. Data was collected through observation, interviews, focus groups discussion, scales and checklists, and documentation. The data analysis was descriptive-analytic that was supported by the quantitative data from social skills scale adapting from SSCSA Walker-McConnell, by comparison the individual or group of subject (empirical mean) with the hypothetical mean scale. The calculation of the percentage of social skills achievement was estimated to support the discussion on improving social skills. The result revealed that the PBS program implementation that began with the behavior assessment could identify problem behaviors pattern of subjects. Social skills enhancement in basic social behavior, interaction with friends, and school adjustments was showed after PBS implementation. General social skills increased from below to above. AM reaches 14.41% of social skills achievement, 11.16% by FJ and 20% by LD. The success of the program was supported by the systematic nature of PBS, multimethods of intervention, school/teacher collaboration, and subjectsâ involvement in the intervention.